Ecological interactions in Pseudomonas aeruginosa - Staphylococcus aureus mixed biofilms: deciphering co-infection in cystic fibrosis airways - Magalhães, Andreia Patrícia Alves (2022)
Tese de doutoramento em Engenharia Química e Biológica